Bien parler, dire vrai. Parrhesia and rhetoric of veridiction in the last Foucault (Nóema, 2013)
Starting from the course at the Collège de France The hermeneutics of the subject, the analysis of the complex relationship between rhetoric and philosophy allows Foucault to reformulate the question of truth from the point of view of the practices veridiction. Compared to philosophy, rhetoric is the way of being different of the discourse through which parrhesia can be defined in its constitutive difference: the testing of a word that is creative "performance", a dramatic of the true as a power of alteration.